Mediating Role of Advertisement Credibility in Beauty Influencer Trust and Local Balinese Skincare Purchases - Febri Purnama Sari, Desak Made; Oka Martini, Ida Ayu; Basmantra, Ida Nyoman; Dinda Savitri Devi, Anak Agung Sagung (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 19 Nomor 1 Tahun 2025, 2025)
Competition in the beauty sector is very competitive, because this industry has many enthusiasts. However, people do not have much knowledge about local skincare products. This study explores the relationship between trust in beauty influencers, advertisement credibility, brand credibility, and the purchase intention of local skincare products. The sample used is  100 Generation Z , the test was conducted  with PLS – SEM. The research findings support six hypotheses. The results indicate that trust in beauty influencers enhances brand trust in skincare products. Generation Z consumers trust advertisements because they offer accurate, comprehensive, and appealing product information, thereby eliciting a purchase intention. Additionally, beauty influencers are perceived as capable of providing honest information, which further influences purchase intention. The implications of this study suggest that effective advertisement credibility can increase consumer intention to purchase local skincare products in Bali. Keywords:  advertisement credibility; beauty influencer trust; brand credibility; purchase intention